2017
DOI: 10.1016/j.joca.2017.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Hyperlipidaemia and incident osteoarthritis of the hand: a population-based case-control study

Abstract: Our results suggest that hyperlipidaemia may be an independent risk factor for new onset HOA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 13 publications
1
30
0
1
Order By: Relevance
“…We also cannot rule out the idea that RA patients limit their manual activity and therefore diminish the mechanical stress on their osteoarthritic joints. The present study results favor the still-uncertain notion that obesity could be a risk factor for hand OA (17) by showing that patients with a higher BMI had a significantly higher risk of development and progression of DIP joint OA.…”
Section: Discussionsupporting
confidence: 81%
“…We also cannot rule out the idea that RA patients limit their manual activity and therefore diminish the mechanical stress on their osteoarthritic joints. The present study results favor the still-uncertain notion that obesity could be a risk factor for hand OA (17) by showing that patients with a higher BMI had a significantly higher risk of development and progression of DIP joint OA.…”
Section: Discussionsupporting
confidence: 81%
“…Eventually, after evaluation of the full texts, eight studies were excluded for the reason that they did not satisfy our inclusion criteria: three studies offered inadequate information [25][26][27], three studies did not offer ORs or RRs for OA or adequate information to calculate these variables [28][29][30], and two studies were removed that either did not have dyslipidemia as an exposure or did not have OA as an outcome [31,32]. Ultimately, nine available observational articles were recognized for our meta-analysis [33][34][35][36][37][38][39][40][41]. Table 1 presents the principal features of the studies included in the meta-analysis, all of which were observational studies.…”
Section: Study Selection and Studymentioning
confidence: 99%
“…The relationship between dyslipidemia and the risk of OA was investigated by three casecontrol studies [33,40,41]. Two case-control studies were population-based, and one case-control study was hospital based.…”
Section: Case-control Studiesmentioning
confidence: 99%
“…However, the role that metabolic factors play in the incidence and progression of hand OA is unclear, as little longitudinal research has been undertaken. Apart from one study that did not find an association between type 2 diabetes and incident hand OA (10), and two studies that examined hyperlipidaemia and incident hand OA with differing results (11,12), most studies have focused on obesity, and conflicting findings have been reported (13)(14)(15)(16)(17)(18)(19)(20)(21)(22). The disparity in results could be due to variations in study populations and the definitions of progression used.…”
mentioning
confidence: 99%